Taking Sides Theories, Practices, and Cultures of Participation in Dissent - Bippus, Elke; Ganzert, Anne; Otto, Isabell (Edition Kulturwissenschaft, 2021)
Is there an option to oppose without automatically participating in the opposed? This volume explores different perspectives on dissent, understanding practices, cultures, and theories of resistance, dispute, and opposition as inherently participative. It discusses aspects of the body as a political instance, the identity and subjectivity building of individuals and groups, (micro-)practices of dissent, and theories of critique from different disciplinary perspectives. This collection thus touches upon contemporary issues, recent protests and movements, artistic subversion and dissent, online activism as well as historic developments and elemental theories of dissent.